2009
DOI: 10.1002/jnr.22178
|View full text |Cite
|
Sign up to set email alerts
|

Parkin reverses intracellular β‐amyloid accumulation and its negative effects on proteasome function

Abstract: The significance of intracellular β-amyloid (Aβ 42 ) accumulation is increasingly recognized in Alzheimer's disease (AD) pathogenesis. Aβ removal mechanisms that have attracted attention include IDE/neprilysin degradation and antibody-mediated uptake by immune cells. However, the role of the ubiquitin-proteasome system (UPS) in the disposal of cellular Aβ has not been fully explored. The E3 ubiquitin ligase Parkin targets several proteins for UPS degradation, and Parkin mutations are the major cause of autosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 81 publications
4
86
0
1
Order By: Relevance
“…The UPS is abnormal in AD [68][69][70][71] and its function is impaired by A␤ 1-42 peptides [8,72,73]. In this study we found that A␤ 1-42 treatment reduces the activities of the three proteosomal enzymes in WT and parkin null cultures.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The UPS is abnormal in AD [68][69][70][71] and its function is impaired by A␤ 1-42 peptides [8,72,73]. In this study we found that A␤ 1-42 treatment reduces the activities of the three proteosomal enzymes in WT and parkin null cultures.…”
Section: Discussionsupporting
confidence: 52%
“…Parkin, as E3 ubiquitin ligase reduces the levels of intracellular proteins by ubiquitination and proteasomal degradation [6,8,53,61]. Parkin, acting through the ubiquitin proteosomal system and stimulating autophagy, ship off altered proteins and mitochondria [33,62].…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that we demonstrated that p53 regulates, and is regulated by, several members of the γ-secretase complex [29,30,31,32,33] responsible for Aβ peptides that accumulate in Alzheimer's disease-affected brains [34]. Indeed, several studies indicated that parkin could control the levels of Aβ [35,36]. It should be noted that we recently delineated a consensus binding sequence targeted by parkin that allowed us to identify presenilins 1 and 2, the catalytic cores of the γ-secretase complex [37] as new parkin transcriptional targets [38].…”
Section: Resultsmentioning
confidence: 99%
“…Parkin overexpression activates the proteasome and facilitates protein clearance in models of neurodegeneration [7,8,68,84,85,86,87]. Parkin-mediated α-synuclein degradation via the ubiquitin-proteasome pathway now appears unlikely, and mounting evidence suggests that α-synuclein is cleared via autophagy [60,69,88,89].…”
Section: Parkin Beyond Pd-linked Mutationsmentioning
confidence: 99%
“…Insoluble Parkin accumulates with intraneuronal β-amyloid (Aβ) in the hippocampus and cortex in association with autophagic defects in AD [18], suggesting that aging contributes to Parkin instability. Wild-type (WT) and not mutant loss-of-function Parkin increases proteasome activity [85,86,87] and degrades ubiquitinated Aβ, while proteasome inhibition leads to accumulation of ubiquitinated protein. Furthermore, several neurotoxins, including rotenone and 6-hydroxydopamine as well as dopamine, alter Parkin solubility and result in its intracellular aggregation [102].…”
Section: Parkin Beyond Pd-linked Mutationsmentioning
confidence: 99%